2001
DOI: 10.1103/physrevlett.86.155
|View full text |Cite
|
Sign up to set email alerts
|

Local Observation of Field Polarity Dependent Flux Pinning by Magnetic Dipoles

Abstract: A scanning Hall probe microscope is used to study flux pinning in a thin superconducting Pb film covering a square array of single-domain Co dots with in-plane magnetization. We show that single flux quanta of opposite sign thread the superconducting film below T(c) at the opposite poles of these dipoles. Depending on the polarity of the applied field, flux lines are attracted to a specific pole of the dipoles, due to the direct interaction with the vortexlike structures induced by the local stray field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
97
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 11 publications
(14 reference statements)
1
97
2
Order By: Relevance
“…Our experiments were performed on a 50 nm granular Pb film (T c ¼ 7:17 K) deposited over an a ¼ 1 lm period square array (H 1 ¼ U 0 =a 2 ¼ 20:67 Oe) of 0.4 lm square ferromagnetic ÔdotsÕ with perpendicular magnetic anisotropy patterned in a [Co(0.3 nm)/Pt(1.1 nm)] 10 multilayer film [5,7,15]. The overall array size was $2 mm · 2 mm and contained about 4 · 10 6 magnetic dots.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experiments were performed on a 50 nm granular Pb film (T c ¼ 7:17 K) deposited over an a ¼ 1 lm period square array (H 1 ¼ U 0 =a 2 ¼ 20:67 Oe) of 0.4 lm square ferromagnetic ÔdotsÕ with perpendicular magnetic anisotropy patterned in a [Co(0.3 nm)/Pt(1.1 nm)] 10 multilayer film [5,7,15]. The overall array size was $2 mm · 2 mm and contained about 4 · 10 6 magnetic dots.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It is now well known that commensurate vortex structures form in these materials at certain specific values of the vortex density when sharp peaks in the bulk magnetisation and critical current are observed [1][2][3][4][5][6][7]. Many different types of artificial pinning object have been successfully realised including arrays of sub-micron holes (antidots) [1][2][3] or ferromagnetic dots with both in-plane [4,5] and perpendicular anisotropy [6,7], yet the qualitative features of the matching phenomena appear to be generic to all of these. The strongest critical current enhancements occur at integer matching fields, when one or more vortices become trapped at each pinning site.…”
Section: Introductionmentioning
confidence: 99%
“…If hard magnets are used, the interaction of the magnetic vortices of the superconductor with the magnetic moments of the ferromagnet may lead to an enhancement of the pinning of the vortices 3,4,5,6 or to an increase of the critical fields 7,15 . Soft magnets, on the other hand, aid to amend superconductor performance by shielding the transport current self-induced magnetic field as well as the externally imposed magnetic field 18,19,20,28,29 .…”
Section: Introductionmentioning
confidence: 99%
“…Heterostructures on the macro or nano scales involving type-II superconductor and ferromagnet elements show great potential for improving superconductor properties such as critical currents and critical fields, and therefore have been extensively studied both experimentally and theoretically during the past few years 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27 . If hard magnets are used, the interaction of the magnetic vortices of the superconductor with the magnetic moments of the ferromagnet may lead to an enhancement of the pinning of the vortices 3,4,5,6 or to an increase of the critical fields 7,15 .…”
Section: Introductionmentioning
confidence: 99%
“…Ferromagnetic particles, fabricated onto a superconductor, have many effects of fundamental interest. Van Bael et al 5 considered a ferromagnetic dot array with magnetic dipole moments parallel to the surface of superconducting substrate. They showed that a flux lattice ͑FL͒ is pinned at the opposite poles of the ferromagnetic dots ͑FDs͒, where flux quanta of opposite signs are induced by the stray field.…”
Section: Introductionmentioning
confidence: 99%